PENINGKATAN TATA KELOLA UMKM JAMU GINGGANG MELALUI PEMASARAN DIGITAL, INOVASI PRODUK, DAN EDUKASI KONSUMEN - Arista Natia Afriany; Pradita Nindya Aryandha; Yennisa Yennisa; Eka Luchiawati; Daniel Amorito Sarumaha; Hanif Mangesti Purbojati; Ainaya Natania Alfatihah; Nabela Nuraini (Komunitas Manajemen Kompetitif, 2025)
Abstract: The Jamu Ginggang MSME, a traditional herbal medicine processing business in Yogyakarta, faces challenges in digital marketing, product innovation, and consumer education. The goal of this community service program is to improve partner governance by optimizing digital marketing strategies, developing product innovations, and strengthening consumer education. The method used is a participatory mentoring approach, encompassing observation, program planning, implementation, and evaluation of activities with partners. The results of the activity indicate the establishment of digital marketing channels through social media and marketplaces, the development of more practical sachet herbal medicine products, and increased consumer awareness of the benefits of traditional herbal products. This activity has had a positive impact on MSMEs in increasing their competitiveness. Therefore, this activity serves as a model for effective collaboration between academia and MSMEs in supporting the sustainability of businesses based on local wisdom.